1998
DOI: 10.1038/bjc.1998.231
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of tumour oxygenation during and after photodynamic therapy in vivo: effects of fluence rate

Abstract: Summary It has been proposed that the generation of 102 during photodynamic therapy (PDT) may lead to photochemical depletion of ambient tumour oxygen, thus causing acute hypoxia and limiting treatment effectiveness. We have studied the effects of fluence rate on P02, in the murine RIF tumour during and after PDT using 5 mg kg-' Photofrin and fluence rates of 30, 75 or 150 mW cm-2. Median P02 before PDT ranged from 2.9 to 5.2 mmHg in three treatment groups. Within the first minute of illumination, median tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
204
1
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(215 citation statements)
references
References 26 publications
5
204
1
2
Order By: Relevance
“…Although our pilot study showed no significant changes in oxygen saturation in either the ten patients monitored during standard MAL-PDT or the ten receiving the OPI intervention, the conclusion made from previous non-interventional oxygen monitoring studies (conducted with larger patient numbers), is that substantial changes in oxygenation can occur during and after PDT [31] and there is little debate surrounding the importance of oxygen during PDT. Oxygen can therefore be consumed in the photochemical reactions required for successful PDT more rapidly than it can be replenished [32].…”
Section: Discussioncontrasting
confidence: 62%
“…Although our pilot study showed no significant changes in oxygen saturation in either the ten patients monitored during standard MAL-PDT or the ten receiving the OPI intervention, the conclusion made from previous non-interventional oxygen monitoring studies (conducted with larger patient numbers), is that substantial changes in oxygenation can occur during and after PDT [31] and there is little debate surrounding the importance of oxygen during PDT. Oxygen can therefore be consumed in the photochemical reactions required for successful PDT more rapidly than it can be replenished [32].…”
Section: Discussioncontrasting
confidence: 62%
“…12 However, in hypoxic conditions, it becomes less accurate for predicting the PDT efficacy since it does not consider the rate of PDT consumption of 3 O 2 for different ϕ. 15,16 With integration of the variation of 3 O 2 concentration (½ 3 O 2 ) into explicit dosimetry, a so-called singlet oxygen explicit dosimetry method based on mathematical modeling to calculate the 1 O 2 has made it possible to predict the PDT outcome. 17 For this purpose, an empirical four-parameter macroscopic 1 O 2 model was developed, and the reacted singlet oxygen (½ 1 O 2 rx ) was proposed as a dosimetry quantity for the accumulated concentration of 1 O 2 that is responsible for cellular killing and clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…(e) Power densities have been varied to study PDTinduced oxygen depletion [53,54], tissue response to PDT [37,55] or hyperthermia effects [56]. We have used two values (33 and 100 mW/cm 2 ) and have kept the light dose constant by varying the irradiation time.…”
Section: Choice Of Treatment Variablesmentioning
confidence: 99%